Pengaruh Proses Tempering Ganda Terhadap Sifat Mekanik Material Baja Cor Paduan Ni-Cr-Mo [The Influence of Double Tempering on Mechanical Properties of Ni-Cr-Mo Cast Steel Alloy] - Bandanadjaja, Beny; Idamayanti, Dewi (Pusat Penelitian Metalurgi dan Material - LIPI, 2017)
This research is conducted in order to find the improvement of steel casting mechanical property, that has been treated on double tempering processes. High toughness is required in order that on the application the steel must has capability of holding the impact load or shock without fracture. Properties of steel in the as-cast condition is quite brittle, the elongation is quite low. In order to improve the toughness, the cast steel can be given additional tempering treatment after normalizing processes. The tempering process will reduce hardness and improve the elongation so that the toughness of the steel material can be increased. The second tempering is required to eliminate the brittle phase that occurs and the elongation of the steel material can be increased. The process of heat treatment which has been applied is normalizing followed with a double tempering temperature variation. The variation of tempering temperature is given to find the best combination of the mechanical properties of strength and elongation. The result showed that the heat treatment processes on Ni, Cr and Mo alloy steel material can increase its elongation without decreasing in tensile strength significantly. In the as-cast condition the steel is very brittle i.e. 4% elongation and impact value of 15 J/Cm2. The heat treatment process which produces high toughness with the best combination of tensile strength and elongation is the process of normalizing followed by first and the second tempering at 650 °C. Mechanical properties result with tensile strength of 68.3 MPa, yield strength of 52.5 MPa and elongation of 20 %. Material toughness is increased after double tempering around 142 J/Cm2.AbstrakPenelitian ini dilakukan dengan tujuan untuk mengetahui perbaikan sifat mekanik material baja cor paduan Cr-Ni-Mo yang telah mengalami proses tempering ganda. Ketangguhan tinggi diperlukan agar dalam aplikasinya baja mampu meredam atau menahan beban impak atau kejut dengan baik. Sifat mekanik baja cor pada kondisi as-cast cukup getas dengan elongasi cukup rendah. Untuk dapat meningkatkan ketangguhannya maka baja cor dapat diberikan perlakuan tambahan yaitu proses tempering setelah normalising. Namun proses tempering yang diberikan dapat pula memunculkan presipitat karbida yang bersifat getas. Oleh karenanya, tempering kedua diperlukan dengan demikian fasa getas yang terjadi dapat dihilangkan serta elongasi baja dapat semakin meningkat. Proses perlakuan panas yang diterapkan adalah proses normalising yang dilanjutkan tempering ganda dengan variasi temperatur tempering, untuk mengetahui kombinasi kekuatan dengan elongasi baja yang terbaik. Hasil yang diperoleh bahwa baja paduan Ni, Cr dan Mo dapat menghasilkan elongasi yang meningkat tanpa diikuti dengan penurunan kekuatan tarik secara signifikan. Pada kondisi as-cast material baja memiliki sifat yang sangat getas yaitu elongasi 4% dan harga impak 15 J/cm2. Proses perlakuan panas yang menghasilkan ketangguhan terbaik dengan kombinasi kekuatan tarik dan elongasi yang tertinggi adalah proses normalising diikuti oleh tempering I dilanjutkan dengan tempering II pada temperatur 650 °C. Sifat mekanik yang dapat dicapai yaitu kekuatan tarik sebesar 68,3 MPa, kekuatan luluh sebesar 52,5 MPa dan elongasi sebesar 20%. Ketangguhan baja cor meningkat setelah tempering ganda menjadi 142 J/Cm2.